Metabolic Reprogramming and Renal Fibrosis - Zhu, Xiaoyu; Jiang, Lili; Long, Mengtuan; Wei, Xuejiao; Hou, Yue; Du, Yujun (Frontiers in Medicine, 2021)
There are several causes of chronic kidney disease, but all of these patients have renal fibrosis. Although many studies have examined the pathogenesis of renal fibrosis, there are still no effective treatments. A healthy and balanced metabolism is necessary for normal cell growth, proliferation, and function, but metabolic abnormalities can lead to pathological changes. Normal energy metabolism is particularly important for maintaining the structure and function of the kidneys because they consume large amounts of energy. We describe the metabolic reprogramming that occurs during renal fibrosis, which includes changes in fatty acid metabolism and glucose metabolism, and the relationship of these changes with renal fibrosis. We also describe the potential role of novel drugs that disrupt this metabolic reprogramming and the development of fibrosis, and current and future challenges in the treatment of fibrosis.